The compression of myometrium and occlusion of uterine artery by COMOC-MG technique for the management of postpartum haemorrhage: clinical perspective from ten cases - Prajapati, Jitendra; Oza, Abhishek; Gupta, Mahesh; Kulkarni, Ketan (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Compression of myometrium and occlusion of uterine artery by Dr. Mahesh Gupta (COMOC-MG) technique is an improved B-lynch stitch technique used to control postpartum hemorrhage (PPH). Objective was to study clinical perspective of the COMOC-MG technique on the effect of PPH in Indian women. Data of 10 patients with PPH who were managed by using the COMOC-MG technique in a tertiary care center in Gujarat from April 2022 to December 2022 were retrieved. Baseline characteristics, medical problems and history of women were recorded. Decision to perform COMOC-MG stitch was taken based on the indications such as PPH, per vaginal bleeding and degree of uterine contractility. Out of 10 women, four women had medical problems such as pregnancy-induced hypertension, dysfunctional uterine bleeding and using psychiatric medicines; two women had uterine surgery/ Laparotomy; four women were diagnosed with ailments such as pregnancy induced hypertension (PIH) and hypertension during the third trimester of pregnancy. Indications such as twins during a previous pregnancy, deflexed head, previous lower segment caesarean section (LSCS) with intrauterine growth restriction (IUGR), breech, prim parity, severe oligohydramnios, placental insufficiency and second baby were considered to carry out the CS delivery. Women were managed by COMOC-MG stitch followed by Misoprostol tablets; Carbetocin, Oxytocin, Methylergometrine and Carboprost injections to control PPH. Mean time between uterine closure to COMOC-MG was 10 min. COMOC-MG stitch resulted in good outcomes in seven patients except one patient had atonic PPH. Out of ten patients, one patient required a hysterectomy and three patients required blood transfusion. COMOC-MG stitch is an easy, simple method to control PPH.